KEABSAHAN HAK GUNA BANGUNAN TERHADAP PUTUSAN PTUN SAMARINDA NOMOR 05/G/2014/PTUN.SMD - Adi Wijaya (Sekolah Tinggi Ilmu Hukum Awang Long, 2017)
The importance of land issues in Indonesia, then the Law of the Republic of Indonesia Number 5 Year 1960 on the Basic Regulation of Agrarian Principles,The purpose of land registration is to provide legal certainty and legal protection to the right holder of a plot of land, apartment units and rights Others who are registered to easily prove themselves as holders of the rights concerned, as well as to provide information to interested parties including the government in order to easily obtain the necessary data in the conduct of legal acts concerning the plots of land and apartment units That have been registered, for the implementation of the orderly administration of land. But in practice, there are many lawsuits filed to the State Administrative Court on land rights, one of which is the building rights